BEAST detection of a brown dwarf and a low-mass stellar companion around the young bright B star HIP 81208 - Viswanathan, Gayathri; Janson, Markus; Gratton, Raffaele; Squicciarini, Vito; Rodet, Laetitia; Ringqvist, Simon C.; Mamajek, Eric E.; Reffert, Sabine; Chauvin, Gaël; Delorme, Philippe; Vigan, Arthur; Bonnefoy, Mickaël; et al. (Astronomy and astrophysics, 2023)
Recent observations by the B-star Exoplanet Abundance Study (BEAST) illustrate the existence of substellar companions around very massive stars. Here, we present the detection of two lower mass companions to a relatively nearby (148.7−1.3+1.5 pc), young (17−4+3 Myr), bright (V = 6.632 ± 0.006 mag), 2.58 ± 0.06 M⊙ B9V star HIP 81208 residing in the Sco-Cen association using the Spectro-Polarimetric High-contrast Exoplanet REsearch (SPHERE) instrument at the Very Large Telescope (VLT) in Chile. Our analysis of the photometry obtained gives mass estimates of 67−7+6 MJ for the inner companion and 0.135−0.013+0.010 M⊙ for the outer companion, indicating that the former is most likely a brown dwarf and the latter a low-mass star. The system is compact but unusual, as the orbital planes of the two companions are likely close to orthogonal. The preliminary orbital solutions we derive for the system indicate that the star and the two companions are likely in a Kozai resonance, rendering the system dynamically very interesting for future studies.
Online veröffentlicht: 03. Juli 2023
Gesehen am 11.10.2023